Model urzędu sędziego w myśli politycznej Leona Chajna - Korzeniewska-Lasota, Anna (PRAWO i WIĘŹ, 2026)
Leon Chajn was one of the key figures in the post-war justice system. A lawyer and politician who first served as deputy head of the Ministry of Justice and then as undersecretary of state in that ministry, he was one of the main architects of the Stalinist transformations in the Polish justice system. In this paper, the author presents Chajn as a prominent post-war figure, above all as a politician. He initially served as deputy head of the Ministry of Justice, and then as undersecretary of state in that ministry. He was one of the main architects of the Stalinist reforms in the Polish justice system. In the justice system. As a lawyer, the author presents Chajn’s views on the ideal judge in the post-war context. These views are reconstructed based on statements published in monographs and magazines, as well as those given during radio broadcasts and at Democratic Party congresses.